A development model of factors affecting customer loyalty to mobile service providers in Thailand - Klankaew, Patcharanan; Saengnoree, Amnuay (My University, 2018)
The purpose of this research is to explore the model of factors affecting customer loyalty to mobile service providers of Thailand. Consequently, this study examined and analysed the causal relation factors of service quality, brand image, customer satisfaction, and switching deterrents on their loyalty. Based on previous empirical studies, this study proposes a structural model of customer loyalty and units of analysis are selected from users of 3 major mobile phone service providers, totalling 400 people. Population sampling is mobile users from the percentage of six areas in Bangkok with multi-stage sampling. A set of questionnaires is used to collect data. An analysis of structural equation modelling using AMOS 21 program is conducted to test the ten hypotheses. This paper provides development model for mobile phone service providers to manage the important influential roles of service quality, brand image and customer satisfaction effect on customer loyalty.
Keywords: Brand image; Customer loyalty; Customer satisfaction; Mobile service providers; Service quality; Switching deterrents; Thailand